Zinc finger protein 267 is up-regulated in hepatocellular carcinoma and promotes tumor cell proliferation and migration - Schnabl, Bernd (2011)
Zinc finger protein 267 (ZNF267) belongs to the family of Kruppel-like transcription factors, which regulates diverse biological processes that include development, proliferation, and differentiation. We have previously demonstrated that ZNF267 mRNA is up-regulated in liver cirrhosis, which is the main risk factor for hepatocellular carcinoma (HCC). Here, we analyzed the expression of ZNF267 in human HCC cells and tissue specimens and found a significant up-regulation compared to primary human hepatocytes and corresponding non-tumorous liver tissue. Over-expression of the transcription factor Ets-1 further enhanced ZNF267 expression, and reporter gene assays revealed that mutation of the Ets-1 binding site to the ZNF267 promotor markedly inhibited ZNF267 promotor activity. Hypoxic conditions induced Ets-1 in HCC cells via HIF1alpha activation, and hypoxia induced ZNF267 expression while HIF1alpha inhibition significantly reduced both hypoxia-induced as well as basal ZNF267 expression in HCC cells. It is known that hypoxic conditions in tumorous tissues induce the formation of reactive oxygen species (ROS), and ROS have been identified as important factor in the regulation of Ets-1 expression in tumor cells. Here, we found that ROS induction induced and ROS scavenging reduced ZNF267 expression in HCC cells, respectively. Loss and gain of function analysis applying siRNA directed against ZNF267 or transient transfection revealed that ZNF267 promotes proliferation and migration of HCC cells in vitro. These findings indicate Ets-1 and HIF1alpha as critical regulators of basal and hypoxia- or ROS-induced ZNF267 expression in HCC, and further suggest that the pro-tumorigenic effect of these factors is at least in part mediated via increased ZNF267 expression in HCC. Since ZNF267 is already elevated in cirrhosis, ZNF267 appears as promising target for both prevention as well as treatment of HCC in patients with chronic liver disease.